VALUES OF CHARACTER EDUCATION IN BUYA HAMKA'S GREAT PERSONAL BOOK - Hendra Alsa Fahmi; Rahmat Hidayat; M. Fauzi Lubis (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
This research method is library research. The aims of this research are, (1). To find out what the values of character education are contained in the great Personal book by Buya Hamka, (2). To find out how the formation of character education values in the Great Personal book by Buya Hamka, (3). To find out how the implications of character education contained in the great Personal book by Buya Hamka which are in the world of education in Indonesia. The results showed that: (1). The values of character education contained in the Great Personal book are (a). Religious, (b). Honest, (c). Tolerance, (d). Discipline, (e). Hard work, (f). Independent, (g). Democratic, (h). National spirit, (i). Love the homeland, (j). Appreciating achievements, (k). Friendly/communicative, (l). Peace-loving, (m). Social care, (n). Likes to read, and (o). Responsibility.